Expanding of Intellectual Possibilities of Digital Tonometers for Home Using - Fainzilberg L.S. (Control systems & computers, 2020)
The purpose of the article is to expand the intellectual capabilities of digital blood pressure monitors, which will increase the efficiency of their use at home. The proposed approach boils down to simple computational procedures that can be implemented on the internal processor of a home blood pressure monitor. It is shown that to assess long-term variability of indicators, it is enough to use the recurrence formulas for each current measurement to correct the range of recorded values, refine the mean and standard deviation, calculate the Pearson coefficient of variation and the index characterizing the percentage of measurements that exceed established medical standards.